An asexual Epichloë endophyte enhances waterlogging tolerance of Hordeum brevisubulatum. (February 2015) - Song, Meiling; Li, Xiuzhang; Saikkonen, Kari; Li, Chunjie; Nan, Zhibiao
Abstract: Using field collected asexual Epichloë endophyte infected (E+) and endophyte free (E−) Hordeum brevisubulatum plants in a greenhouse experiment, we demonstrate that endophyte infection increases host plant resistance to waterlogging. All plants assigned to waterlogging treatment started to wither and lose their root vitality, and consequently lost considerable photosynthesizing and root tissues. However, E+ plants showed significantly less symptoms of damage, and they produced significantly greater content of chlorophyll, more tillers, higher shoots and higher under-ground biomass compared to E− plants. Waterlogging induced osmoprotective proline production particularly in E+ plants and had lower malondialdehyde content and electrolyte leakage, suggesting that endophyte infection positively affects osmotic potential and oxidative balance of the host plant. We propose that higher resistance of E+ plants of H. brevisubulatum to waterlogging should be acknowledged in breeding programmes and the scenarios of changes in grassland ecosystems as a result of climate change.